Porous aluminum oxide for battery separator, battery separator, battery, and electrical equipment

By using porous alumina particles with mesoporous distribution on the surface and inside of the battery separator, the problem that the relationship between the battery separator material and the charge and discharge ratio has not been paid attention to, and the charge and discharge ratio optimization of the lithium-ion battery is achieved, and the overall performance of the battery is improved.

CN119038967BActive Publication Date: 2025-03-25SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411525868.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-25
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

In the prior art, the relationship between the coating material in the battery separator and the charge and discharge ratio of the ion battery has not received enough attention, which makes it difficult to achieve the charging and discharge ratio optimization.

Method used

Porous alumina particles with mesoporous distribution on the surface and inside are used as the separator coating material, and their specific surface area is controlled to be in the range of 10~50m2/g and the apparent equivalent diameter is in the range of 0.006μm~0.05μm to optimize the charge and discharge rate of lithium-ion batteries.

Benefits of technology

By using porous alumina particles, the charge and discharge rate of lithium-ion batteries is significantly improved, especially when the charge and discharge rate (such as 5C), which improves the cycle performance, safety performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038967B_ABST
    Figure CN119038967B_ABST
Patent Text Reader

Abstract

The present invention provides a porous alumina for battery diaphragm, a diaphragm, a battery, and an electrical device, and relates to the technical field of diaphragm materials. The porous alumina includes alumina particles with a plurality of mesopores distributed on the surface and inside. The specific surface area of ​​the porous alumina is between 10 and 50 m 2 / g in this range; the specific volume v (cm 3 The ratio of the specific surface area of ​​the porous alumina to the specific surface area BET of the porous alumina is D bet Satisfies the following formula: 0.006μm<D bet <0.05 μm. The present application also provides a diaphragm, a battery, and an electrical device based on the porous alumina. The porous alumina provided in the present application can optimize the 5C rate of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of diaphragm materials, and in particular to porous alumina for battery diaphragms, battery diaphragms, batteries, and electrical equipment. Background Art

[0002] The battery charge and discharge rate (C-rate) is used to measure the speed of battery charging and discharging. The higher the battery charge and discharge rate, the faster the charging speed; the lower the battery charge and discharge rate, the slower the charging speed. Therefore, this parameter is one of the more critical parameters in battery applications.

[0003] The optimization of the charge and discharge rate of ion batteries is currently mainly focused on the optimization of electrolytes and electrodes, that is, it is mainly focused on improving or optimizing the charge and discharge rate of ion batteries by improving the formula or shape of the electrolyte, the activity performance of the electrode material, etc.

[0004] However, less attention has been paid to the relationship between the materials in the diaphragm, especially the coating materials of the diaphragm, and the charge and discharge rates of ion batteries. Summary of the invention

[0005] The object of the present invention is to provide a porous alumina for battery separators. The particles of the porous alumina are applied in separator coatings to optimize the charge and discharge rates of ion batteries.

[0006] Another object of the present invention is to provide a battery separator.

[0007] Another object of the present invention is to provide a battery.

[0008] Another object of the present invention is to provide an electrical device.

[0009] In a first aspect, the present application provides a porous alumina for a battery separator, wherein the porous alumina comprises alumina particles having a plurality of mesopores distributed on the surface and inside; the porous alumina has a specific surface area of ​​10 to 50 m 2 / g this range;

[0010] The apparent equivalent diameter D of the porous alumina bet The value satisfies the following formula:

[0011] 0.006μm<D bet <0.05μm

[0012] Among them, the apparent equivalent diameter D bet is the specific volume v of porous alumina (cm 3 The specific volume is the reciprocal of the volume density of alumina particles containing a certain number of mesopores.

[0013] Furthermore, in some embodiments of the present application, 0.01 μm<D bet <0.03μm.

[0014] Furthermore, in some embodiments of the present application, the aluminum oxide particles are single crystal particles.

[0015] Furthermore, in some embodiments of the present application, the ratio of the short side of the bottom surface of the aluminum oxide particle to the height of the aluminum oxide particle is 1:(0.3~1.5).

[0016] Further, in some embodiments of the present application, the porous alumina includes at least one of α-alumina, θ-alumina, and δ-alumina.

[0017] Further, in some embodiments of the present application, the porous alumina does not include γ-alumina.

[0018] Furthermore, in some embodiments of the present application, each particle in the porous alumina includes a plurality of pores, and the pore diameter is 2-50 nm.

[0019] Further, in some embodiments of the present application, the proportion of the pores in the alumina particles to the alumina particles is not less than 60%; wherein the proportion of the pores in the alumina particles to the alumina particles is determined by the following method:

[0020] A transmission electron microscope (TEM) image of the aluminum oxide particles is obtained using a transmission electron microscope, the grayscale of the transmission electron microscope image is adjusted so that the grayscale of the pixel with the highest grayscale is adjusted to 255, and the ratio of the total number of pixels with a grayscale not higher than 100 within the range of the aluminum oxide particles in the transmission electron microscope image to the total number of pixels within the range of the aluminum oxide particles in the transmission electron microscope image is counted.

[0021] Furthermore, in some embodiments of the present application, the proportion of pores in the alumina particles is not less than 80% of the alumina particles.

[0022] Furthermore, in some embodiments of the present application, the particle size distribution D50 of the porous alumina is 0.3-20 μm, and the value of D50 / (D90-D10) of the porous alumina is not higher than 1.

[0023] In a second aspect, the present application further provides a battery separator, comprising a base membrane and a coating formed on at least one side of the base membrane, wherein the porous alumina described in the first aspect is distributed in the coating.

[0024] Furthermore, in some embodiments of the present application, the content of porous alumina in the coating is 75% to 95%, and the surface density of the coating per unit thickness is not higher than 2 g / (m 2·μm).

[0025] In a third aspect, the present application further provides a battery, comprising the battery separator described in the second aspect.

[0026] In a fourth aspect, the present application also provides an electrical device, comprising the battery described in the third aspect.

[0027] The present application provides a porous alumina for battery separator, an electronic component, a battery, and an electrical device. The porous alumina has a large number of mesopores on the surface and inside. When used in the separator, the defect of increased coating surface density caused by the addition of inorganic fillers can be significantly reduced while maintaining the ionic conductivity of the separator. At the same time, the porous alumina has excellent dispersibility and good stability, which is conducive to improving the cycle performance, safety performance and service life of the battery based on the alumina. When its specific volume v (cm 3 / g) and the ratio of the specific surface area BET D bet When the diameter is within the range of 0.006μm~0.03μm, the charge and discharge rate of the lithium-ion battery based on the porous alumina-coated separator is significantly improved, especially at high charge and discharge rates (such as 5C), the improvement is particularly obvious, which is beneficial to the application of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 TEM image of porous alumina prepared in Example 1;

[0029] Figure 2 The charge and discharge rate curves of the button battery formed by the porous alumina prepared in Example 1 and the alumina used in Control Example 1. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] [Specific volume v]

[0032] The specific volume v mentioned in this application is the ratio of the apparent volume of the solid particle material to the mass, wherein the apparent volume is the sum of the solid volume of the solid particle and the volume of the closed pores and the volume of the open pores. The mass here is the mass of the solid particle weighed on a balance.

[0033] [Apparent equivalent diameter D bet ]

[0034] The apparent equivalent diameter D mentioned in this application is bet It is the apparent average particle size in micrometers (μm), and its formula is:

[0035] D bet =v / BET

[0036] Wherein, BET is the specific surface area of ​​the particle, and v is the specific volume of the particle.

[0037] Apparent equivalent diameter D bet The equivalent diameter of a sphere or projected circle that indicates the presence of several holes on the surface and inside of a particle. The larger the apparent equivalent diameter, the lower the specific surface area of ​​the particle and the larger the specific volume. Alumina particles with larger specific surface areas are more difficult to dry and dehydrate, have higher affinity for water, and have larger specific volumes. Alumina particles with larger specific volumes have lower apparent densities, and alumina particles with densities closer to true densities have higher quality and are less conducive to lightweight coatings.

[0038] Alumina is an inorganic ceramic material with excellent chemical stability, high strength and a wide source of raw materials. Spherical alumina, in particular, has good dispersibility and the uniformity of the coating formed is excellent, making it an excellent inorganic filler for diaphragm coatings. However, there are still some problems to be solved when applying alumina to diaphragm coatings. One of the main problems is that the coating formed by spherical alumina particles has poor thermal shrinkage. In addition, non-porous alumina particles will cause a significant loss in the ion conductivity of the diaphragm, and the high density of alumina will cause the surface density of the diaphragm coating to be too high. Therefore, alumina with good thermal shrinkage improvement, maintained ion conductivity and low density is required.

[0039] In this regard, researchers in this field are committed to finding better ceramics for diaphragm coatings. For this purpose, porous alumina is proposed. However, the porous alumina particles provided in the prior art are easy to react with the electrolyte because of their large specific surface area, strong activity or water content that is difficult to reduce to the required range, resulting in poor safety of the battery used in them; at the same time, the dispersibility of alumina with a high specific surface area is also poor, and it is difficult to coat, especially for thinner coatings, such as coatings less than 3μm thick. To this end, the inventor is committed to providing an alumina with a low specific surface area and low water content that is beneficial to battery safety. In the process, the inventor unexpectedly discovered that the alumina provided in this application not only has a low water content, which is beneficial to the safety of the battery, but also is beneficial to the high charge and discharge rate of the battery within a specific low surface equivalent diameter range.

[0040] The aluminum oxide particles provided in the present application are mixed crystal particles with a plurality of mesopores (2-50 nm) distributed on the surface and inside. The specific surface area of ​​the porous aluminum oxide is between 10 and 50 m2 / g; and its apparent equivalent diameter D bet Falling within the range of 0.006μm<Dbet<0.05μm. In order to reduce the surface density of the coating of the battery separator and make the separator lighter, it is extremely effective to form a number of pore structures on the surface of alumina to reduce the density of the alumina used in the coating. However, if there are too many pores on the alumina, its drying and water removal effect will be reduced. At the same time, it is very easy to bond with compounds containing hydroxyl groups and other active groups, resulting in reduced dispersibility and stability, which is not conducive to the reliability optimization of the battery. In order to solve this technical problem, the applicant found that by controlling the apparent equivalent diameter of alumina within the range of 0.006μm~0.03μm, the coating formed by alumina is significantly lighter, and the surface hydroxyl content after drying is also extremely low (the surface hydroxyl content can reach ≤8 / nm 2 , and even the surface hydroxyl content can reach ≤5 / nm 2 ), which is beneficial to improving the reliability of the battery. In addition, when the apparent equivalent diameter of the alumina particles is controlled within this range, the diameter of the pores in the alumina is mostly within the mesoporous range, and the number is large, which can provide more channels for ion conduction.

[0041] In addition, the inventors unexpectedly discovered that when the apparent equivalent diameter of the aluminum oxide provided in the present application is within this specific range, the high charge and discharge rate of the lithium-ion battery based on the aluminum oxide-coated diaphragm is significantly optimized, especially the 5C charge and discharge rate of the lithium-ion battery, which is optimized from about 75% to more than 80%. Furthermore, the apparent equivalent diameter of aluminum oxide is preferably controlled in the range of 0.01μm~0.03μm; more preferably, it is controlled in the range of 0.01μm~0.02μm. When the apparent equivalent diameter of aluminum oxide is within this specific range, the 5C charge and discharge rate of the lithium-ion battery based on the aluminum oxide-coated diaphragm is even optimized to more than 85%. In addition, it should be noted that the specific surface area of ​​the aluminum oxide provided in the present application also needs to be controlled in the range of 10~50m 2 / g, this is because compared with the ultra-high specific surface area (such as 150m 2 / g or more), it is easier to form alumina powder with lower water content than alumina with low specific surface area. The water content in the alumina powder is more stable during storage, and it is not easy to have defects such as agglomeration and adhesion. However, alumina powder with ultra-high specific surface area, especially nano-scale or submicron-scale alumina powder, often has defects such as difficulty in removing water and fast agglomeration due to its good hydrophilicity and high specific surface area, which is not conducive to its application in diaphragm coating.

[0042] The specific surface area of ​​the alumina provided in the present application is relatively high, which is mainly provided by the particle size of the particles and the mesopores distributed on the particles. In the process, the inventors found that the pore size of the mesopores on the alumina particles provided in the present application is preferably 5~50nm, and more preferably 8~20nm; the pores are mainly open holes and through holes, and it is found that the mesopores with a pore size of not less than 8nm are more conducive to the conduction of metal ions such as lithium ions and the absorption and storage of electrolytes, providing a channel for the optimization of ion conductivity. In addition, the pore size of the open holes or through holes on the porous alumina is mainly within 50nm, and even mainly concentrated at 20nm, which is more obvious for the optimization of the conduction of metal ions such as lithium ions and the absorption and storage of electrolytes. The reason may be that the mesopores within this pore size range can reduce the amount of binder used in the coating that enters the mesopores, reduce the amount of binder used, and leave space for the absorption and storage of electrolytes. Preferably, the specific surface area of ​​the porous alumina provided in the present application is 10~50m 2 / g, more preferably 15 to 40 m 2 / g, more preferably 15 to 30 m 2 / g.

[0043] In order to further study whether the apparent equivalent diameter of the alumina particles is controlled within the range of 0.01 μm to 0.02 μm, which is beneficial to the reliability optimization of the battery, the applicant observed the morphology of the alumina particles provided in the present application by transmission electron microscopy, and found that when the apparent equivalent diameter of the alumina particles is controlled within the above range, the proportion of the pores in the alumina particles to the alumina particles is not less than 60%; wherein the proportion of the pores in the alumina particles to the alumina particles is determined by the following method:

[0044] A transmission electron microscope (TEM) image of the aluminum oxide particles is obtained using a transmission electron microscope (TEM) and the grayscale of the TEM image (a TEM image with a scale of 50 nm and a transmission electron microscope of 70,000 times) is adjusted so that the grayscale of the pixel with the highest grayscale is adjusted to 255. The ratio of the total number of pixels with a grayscale not higher than 100 within the range of the aluminum oxide particles in the TEM image to the total number of pixels within the range of the aluminum oxide particles in the TEM image is counted.

[0045] In addition, the applicant studied the grayscale range of each pixel within the range of aluminum oxide particles in the transmission electron microscope image, wherein the total amount of pixels within the grayscale range of 0 to 60 accounts for about 20 to 50% of the total amount of pixels within the range of aluminum oxide particles in the transmission electron microscope image, and the total amount of pixels within the grayscale range of 60 to 100 accounts for about 10 to 47% of the total amount of pixels within the range of aluminum oxide particles in the transmission electron microscope image. The possible reason may be that there are not only a large number of through holes and openings on the aluminum oxide particles provided in the present application, but also some closed holes. The existence of these closed holes provides space for the lightweight of aluminum oxide particles, while the through holes and openings provide channels for ion conduction, but also provide space and sites for the hydrophilicity of aluminum oxide. Therefore, the proportion of pores in the aluminum oxide particles provided in the present application to the aluminum oxide particles is preferably not less than 90%, and the total amount of pixels within the grayscale range of 60 to 100 accounts for about 30 to 47% of the total amount of pixels within the range of aluminum oxide particles in the transmission electron microscope image.

[0046] In the present application, considering the uniformity of the particle size and the effective thickness of the aluminum oxide particles coated on the base film, the particle size distribution of the aluminum oxide particles is preferably an aluminum oxide particle whose D50 is controlled within 0.3-2 μm, D50 / (D90-D10) is controlled within 1, and whose apparent equivalent diameter D bet is controlled within the range of 0.01μm~0.02μm, and D50 is proportional to the apparent equivalent diameter D bet The ratio D50 / D bet The ratio of D50 / D is preferably controlled within the range of 20 to 100. bet When the ratio of D50 / D is within the range of 20 to 100, on the basis of satisfying the dispersibility and reliability of the battery based on the aluminum oxide, the formed coating is not only conducive to high charge and discharge rate performance, but also has excellent surface uniformity and effective thickness of the coating, which is beneficial to the safety of the battery, and is also more conducive to the formation of a thin coating, making the lightweight coating more excellent. More preferably, D50 / D bet The ratio is 20~80.

[0047] Preferably, the D50 of the porous alumina provided in the present application is 0.4 μm to 1 μm, more preferably 0.5 μm to 0.6 μm. More preferably, the ratio between the modal diameter and the D50 particle size of the porous alumina provided in the present application is 0.94-1.16; the particle size distribution of the porous alumina provided in the present application is a normal distribution or infinitely close to a normal distribution.

[0048] It should be noted that the D50 particle size in this application refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D90 refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%; D10 refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 10%; the mode diameter is the particle size corresponding to the maximum frequency density of the particle size distribution.

[0049] The mixed crystalline porous alumina particles provided in this solution refer to: the porous alumina includes at least one of α-alumina, θ-alumina, and δ-alumina. However, the amount of alumina particles with a spherical structure, a quasi-spherical structure, a needle-shaped structure, or a thin-sheet structure is not more than 5% by mass.

[0050] In this embodiment, the morphology of the mixed crystal porous alumina particles is that the ratio of the short side of the bottom surface to the height of the alumina particles is usually in the range of 1: (0.3-1.5).

[0051] In the present application, alumina particles with a spherical or quasi-spherical morphology refer to particles with a spherical or quasi-spherical morphology, such as alumina particles with a sphericity of not less than 95% or higher. Alumina particles with a needle-shaped morphology refer to alumina particles with a conical, quasi-conical, rod-shaped, strip-shaped or similar morphology; alumina particles with a flake structure refer to alumina particles with a layered structure that is flaky or nearly flaky or a plurality of flaky structures; in the single-layer structure of the flaky or layered structure constituting the alumina particles, the ratio of the edge length to the side length of the end face is not less than 10, or even not less than 20, which is obviously manifested as a flake structure in which the edge height is much lower than the side length of the end face.

[0052] The mixed crystalline porous alumina provided in the present application has good morphology consistency and can also improve the flatness and mechanical strength of the coating, which is beneficial to reducing the coating weight of the diaphragm while maintaining the same coating performance.

[0053] In the porous alumina provided in the present application, the particles in the porous alumina are at least one of α-alumina, θ-alumina, and δ-alumina. It is preferred that γ-alumina is not included, or the content of γ-alumina in the porous alumina provided in the present application is not more than 5% by mass, so as to improve the chemical stability of the porous alumina and reduce the activity.

[0054] That is, the porous alumina provided in the present application can be pure phase of θ-alumina and mixed phase alumina with other phases, pure phase of δ-alumina, and pure phase of α-alumina and mixed phase alumina with other phases.

[0055] In some embodiments, the content of metal elements in the porous alumina is: the content of metal elements in the porous alumina is: sodium ion content: 0-500ppm; calcium ion content: 0-300ppm; iron ion content: 0-200ppm; silicon ion content: 0-300ppm; cobalt ion content: 0-50ppm; copper ion content: 0-50ppm; zinc ion content: 0-50ppm; lead ion content: 0-50ppm; chromium ion content: 0-50ppm; nickel ion content: 0-50ppm; zirconium ion content: 0-3000ppm; tin ion content: 0-50ppm.

[0056] More preferably, the sum of the contents of the metal elements in the porous alumina is not higher than 5000 ppm. More preferably, the sum of the contents of the iron element, the cobalt element, the chromium element, the zinc element, and the nickel element in the porous alumina is not higher than 500 ppm, so as to avoid the side reactions of the impurity elements with the electrolyte and the positive and negative electrodes during the charge and discharge process of the battery, increase the consumption of the electrolyte, generate gas, and reduce the ion conductivity, which is conducive to reducing the damage of these impurities to the battery.

[0057] The sum of the contents of metal elements such as iron, cobalt, chromium, zinc and nickel in the porous alumina provided by the present application can reach less than 0.1ppm. The reason may be that the porous alumina particles provided by the present application are mainly single crystal particles, and the integrity of the crystal particles is relatively high; and in the preparation process, the porous formation is not formed by granulation, but by the escape of water molecules in the crystal particles and the displacement of atoms during the crystal phase change process; it makes it difficult for metal elements to embed into the porous alumina particles and attach to the surface of the particles, making it easier for other metal ions in ionic state to remain in the reaction system and be removed by cleaning or demagnetization and impurity removal.

[0058] Preferably, the porous alumina provided in the present application is directly prepared from raw materials without compounding, sorting and mixing of multiple porous aluminas.

[0059] In this regard, in order for those skilled in the art to better understand and implement the present application, a preparation method for preparing the above-mentioned porous alumina is also provided below.

[0060] Preparation method:

[0061] Step (1): providing aluminum hydroxide, seed crystals, dispersant and pure water, mixing aluminum hydroxide, dispersant and pure water, grinding for 1h~12h, immediately adding seed crystals, mixing and simultaneously heating to 150°C~240°C, stirring and reacting for 8h~60h; obtaining an intermediate; controlling the reaction pressure to 1.5~3MPa;

[0062] Step (2): Acid adjustment, demagnetization, drying, calcination at 600°C to 1200°C for 0.5h to 5h, and jet milling to obtain porous alumina powder.

[0063] The dispersant is polycarboxylate; in the system formed by aluminum hydroxide, dispersant and pure water, the amount of dispersant added is 0.01-1% by mass fraction; the amount of aluminum hydroxide added is 10-30% by mass fraction. The amount of seed added is 0.01-0.2% of the system. It should be noted that the particle size of the seed is not higher than 100nm.

[0064] After the intermediate is obtained and before demagnetization, the pH value of the intermediate slurry is adjusted to 7-8.5, preferably 7.5-8.0, with an organic acid, and then demagnetization is performed, and the intermediate slurry is dried by a drying method. The drying method can be spray drying or infrared microwave drying. When spray drying is adopted, a disintegration process is also included after spray drying and before calcination, and the dried particles are dispersed into 0.2-5 μm by air jet milling or grinding.

[0065] The drying method is also preferably infrared microwave drying. Similarly, when infrared microwave drying is used, the dried intermediate powder does not need to be broken up or crushed, and can directly enter the calcination process, saving costs and improving the morphological integrity of the product. In addition, in order to achieve a good dispersion effect, when infrared microwave drying is used, the slurry after demagnetization is first filtered into a filter cake with a free water content of not less than 60%, and then broken into small pieces of filter cake, and then heated to a temperature of not less than 150°C by infrared light irradiation, after 8 to 15 minutes of treatment, the temperature is then reduced to 80 to 100°C, and microwave heating is used for 3 to 10 minutes, and then microwave heating is used to raise the temperature to above 150°C until the small filter cake automatically explodes into powder. Similarly, the intermediate powder formed by segmented drying using an infrared microwave drying process has a low moisture content, which can reach a moisture content (free water) of no more than 0.2%. In addition, during this process, the appearance of the particles is not damaged by grinding or ball milling, and the integrity is better. Moreover, since there is no high-temperature spraying process and automatic explosion into powder, the crystal particles in the obtained powder are less likely to agglomerate, and the single crystal dispersion of the product is better.

[0066] The intermediate prepared thereby also has a crystalline water content of no more than 35% by mass fraction, preferably a crystalline water content of no less than 5%, preferably a crystalline water content of no less than 16%, and a mainly quadrangular prism-shaped morphology, with a particle size mainly distributed in the range of 0.2 to 5 μm.

[0067] Similarly, in step (2), a small amount of a barrier agent that can be decomposed into gas at a relatively low temperature is added, and the decomposition temperature of the barrier agent is not higher than 450°C, more preferably not lower than 50°C and not higher than 100°C. Exemplarily, the barrier agent can be ammonium bicarbonate, ammonium carbonate, ammonium nitrate, preferably ammonium carbonate; the amount of the barrier agent is 0.01% to 0.1% by mass of the dried intermediate powder obtained in step (2). The barrier agent can be added in the drying stage or in the calcination stage. When it is added in the calcination stage, it can also reduce the adhesion of particles to the wall of the container used for calcination during the calcination process. The temperature curve of the calcination process is preferably: rapidly heating to at least 250°C at a heating rate of not less than 5°C / s, reducing the heating rate (heating rate is not higher than 1°C / s) and then heating to the holding temperature, and then sintering for 0.5h to 5h to obtain the product, so as to promote the single crystal morphology of the porous alumina particles to be maintained, and the pore size and pore volume to be controlled.

[0068] In this preparation method, the inventors found that directly adjusting the acidity of the slurry after the reaction can promote the consistency of the crystal structure and particle size of the product and the pore size distribution. The reason may be that directly adjusting the acidity after the reaction can curb the formation of alumina trihydrate, so that the intermediate obtained has higher purity, and a large number of defects appear on the intermediate, providing biased guidance for the subsequent formation and development of pores.

[0069] In addition, the applicant found that the apparent equivalent diameter D in the porous alumina provided by the present application is bet The control of the apparent equivalent diameter D of the alumina can be achieved by controlling the morphology, particle size, water content of the intermediates in the preparation process of porous alumina, as well as the defects on the intermediates and the calcination temperature curve. bet The diameter of the pores in the alumina particles is controlled within the range of 0.006~0.05μm. This may be because the pore development process in the alumina particles should be further controlled on the basis of the morphology of the alumina itself, so that the alumina particles formed based on the intermediates can maintain the morphology and particle size of the intermediates as much as possible, and the distribution, pore size and type of the pores formed can make the apparent equivalent diameter D in the porous alumina bet falls within the required range.

[0070] In a second aspect, the present application further provides a battery separator, comprising a base membrane and a coating formed on at least one side of the base membrane, wherein the porous alumina described in the first aspect is distributed in the coating.

[0071] The content of porous alumina in the coating is 75% to 95%, and the surface density of the coating per unit thickness is not higher than 2g / (m 2 ·μm), especially not higher than 1.5g / (m 2If the solid content of porous alumina ceramic material in the coating is further reduced, the surface density of the coating per unit thickness can be further reduced, even to 1g / (m 2 ·μm), making it more lightweight. However, based on the considerations of coating strength and heat shrinkage optimization, the content of aluminum oxide in the coating should not be too low.

[0072] In a third aspect, the present application further provides a battery, comprising the battery structure described in the second aspect.

[0073] The 5C charge and discharge rate of the battery provided in this application can reach more than 80%, and has good application prospects.

[0074] In a fourth aspect, the present application further provides an electric device, comprising the battery described in the third aspect. The electric device may be an electric vehicle, an aircraft, an aircraft, a mobile phone, a tablet computer, a handheld game console, a portable digital device (such as a digital camera), a smart home, a smart wearable (such as a smart bracelet, a smart watch, smart glasses), or any other electric device that can use an ion battery.

[0075] In order to facilitate those skilled in the art to understand the innovation of the present application, some preferred embodiments are provided below in conjunction with the accompanying drawings to illustrate the above technical solution.

[0076] Example 1

[0077] This embodiment provides a method for preparing porous alumina, comprising the following steps:

[0078] Aluminum hydroxide, bentonite SD-1 and pure water are added into a reaction container in a mass ratio of 30:0.5:69.5, stirred and ground at a frequency of 10-50 Hz for 4-7 hours, and then seeds with an average particle size of 80 nm are immediately added. The amount of seeds added is 0.1% of the system by mass fraction; the loading amount of the reaction container is maintained within the range of 50-80% of the volume;

[0079] The temperature was raised to 180°C at a rate of 5°C / min and kept at this temperature for 50 hours; the pressure in the reaction vessel was maintained at 2.12 MPa to obtain a slurry;

[0080] The slurry is adjusted to pH 8.0 with pure water and oxalic acid, and the solid content is diluted to 15%; then the slurry is demagnetized and spray-dried at 200-220°C to obtain spray particles; the spray particles are jet-milled to obtain intermediate particles with a particle size mainly distributed in the range of 0.2-5 μm;

[0081] By mass fraction, 0.01% ammonium carbonate was added to the intermediate particles, mixed evenly, and then the temperature was rapidly raised to 250°C at a heating rate of not less than 5°C / min, the heating rate was reduced to 1°C / min, and then the temperature was raised to 1100°C, and then sintered for 2 hours to obtain porous alumina. Figure 1 .

[0082] Example 2

[0083] This embodiment provides a method for preparing porous alumina, comprising the following steps:

[0084] Aluminum hydroxide, bentonite SD-1, n-butanol and pure water are added into a reaction vessel in a mass ratio of 30:0.5:20:49.5, stirred and ground at a frequency of 10-50 Hz for 4-7 hours, and then seeds with an average particle size of 80 nm are immediately added. The amount of seeds added is 0.1% of the system by mass fraction; the loading amount of the reaction vessel is maintained within the range of 50-80% of the volume;

[0085] The temperature was raised to 180°C at a rate of 5°C / min and kept at this temperature for 50 hours; the pressure in the reaction vessel was maintained at 2.8 MPa to obtain a slurry;

[0086] The pH value of the slurry is adjusted to 8.0 with pure water and oxalic acid, and the solid content is diluted to 15%. After demagnetization, the filter cake is formed by filter pressing, and the solid content in the filter cake is not less than 65%; the filter cake is broken into small pieces with a diameter of no more than 3 cm, and then the temperature of the small pieces of filter cake is raised to 80°C by infrared light. The infrared is turned on during the whole drying process, and the infrared temperature is about 150°C. After drying for 10 minutes, the temperature of the small pieces of filter cake is raised to 100°C by infrared light, so that the water inside the filter cake gradually begins to evaporate. After drying for 7 minutes; the temperature of the small pieces of filter cake is raised to 150°C by microwave, so that the water inside and outside the material will evaporate to less than 0.2% and automatically explode to present a powder state, and intermediate particles with a particle size mainly distributed in the range of 0.2~5μm are obtained;

[0087] 0.1% ammonium carbonate was added to the intermediate particles by mass fraction, and after uniform mixing, the temperature was rapidly increased to 250°C at a heating rate of not less than 5°C / min, the heating rate was reduced to 1°C / min, and the temperature was increased to 1000°C. The mixture was then sintered for 4 hours to obtain porous alumina.

[0088] Example 3

[0089] This embodiment also provides a method for preparing porous alumina. Compared with Example 2, the pressure in the reaction container is controlled to be 1.5 MPa, and the remaining preparation steps are the same as those in Example 2 to obtain porous alumina.

[0090] Example 4

[0091] This embodiment also provides a method for preparing porous alumina. Compared with Example 2, the pressure in the reaction container is controlled to be 3.0 MPa, and the remaining preparation steps are the same as those in Example 2 to obtain porous alumina.

[0092] Example 5

[0093] This embodiment also provides a method for preparing porous alumina. The pH value of the slurry is adjusted to 8.5 using pure water and oxalic acid, and the solid content is diluted to 15%. The remaining preparation steps are the same as those in Example 2 to obtain porous alumina.

[0094] Example 6

[0095] This embodiment also provides a method for preparing porous alumina, adding 0.1% ammonium carbonate to the intermediate particles, mixing evenly, rapidly heating to 300°C at a heating rate of 5°C / min, reducing the heating rate to 2°C / min, and then heating to 1000°C, and then sintering at this temperature for 4 hours to obtain porous alumina. The remaining preparation steps are the same as those in Example 2 to obtain porous alumina.

[0096] Example 7

[0097] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the reaction temperature is 150° C., the pressure in the reaction container is controlled to be 1.5 MPa, and the remaining preparation steps are the same as Example 1 to obtain porous alumina powder.

[0098] Example 8

[0099] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the reaction temperature is 240° C., the pressure in the reaction container is controlled to be 3.0 MPa, and the remaining preparation steps are the same as Example 1 to obtain porous alumina powder.

[0100] Comparative Example 1

[0101] Compared with Example 1, the pressure in the reaction container in this comparative example is controlled to be 1.0 MPa, and the remaining steps are the same as those in Example 1 to obtain a comparative sample.

[0102] Comparative Example 2

[0103] Compared with Example 1, the step of adjusting the pH value of the slurry to 8.0 using pure water and oxalic acid and diluting the solid content to 15% was omitted in this comparative example, and the remaining steps were the same as those in Example 1 to obtain a comparative sample.

[0104] Comparative Example 3

[0105] Compared with Example 1, in this comparative example, the pH value of the slurry was adjusted to 8.0 by using oxalic acid without dilution, and the remaining steps were the same as those in Example 1 to obtain a comparative sample.

[0106] Comparative Example 4

[0107] Compared with Example 1, ammonium carbonate was not added during the calcination process in this comparative example, and the remaining steps were the same as those in Example 1 to obtain a comparative sample.

[0108] Comparative Example 5

[0109] Compared with Example 1, the calcination temperature curve in this comparative example is to directly increase the temperature to 1200°C at a rate of not less than 5°C / min, and then sinter for 2 hours to obtain porous alumina. The remaining steps are the same as in Example 1 to obtain a comparative sample.

[0110] Comparative Example 6

[0111] Compared with Example 1, the calcination temperature curve in this comparative example is to directly increase the temperature to 600°C at a rate of 0.5°C / min, and then sinter for 2 hours to obtain porous alumina. The remaining steps are the same as those in Example 1 to obtain a comparative sample.

[0112] test

[0113] 1. Particle size

[0114] The test was carried out using a Mastersizer 3000 laser particle size analyzer.

[0115] 2.D bet

[0116] The density ρ was measured by the pycnometer test method, and the specific volume v=1 / ρ was calculated by the formula; BET was measured by Micromeritics physical adsorption instrument 3030; the apparent equivalent diameter D can be obtained by the following formula bet :

[0117] D bet =v / BET.

[0118] 3. Surface hydroxyl content

[0119] The test was carried out using the NaOH titration method.

[0120] 4. Surface density = ceramic layer weight / ceramic layer area

[0121] The mass of the base film before coating is measured by a balance, and the mass m1 of the base film of a predetermined area A is calculated. The diaphragm formed after coating with the ceramic coating is cut into diaphragm samples of a predetermined area A and weighed to obtain m2. The surface density of the coating can be obtained using the following calculation formula: ρsurface=(m2-m1) / A.

[0122] Coating surface density per unit thickness / (g / m 2 *um): Coating surface density per unit thickness = ceramic layer weight / ceramic layer area*um. ρ surface = (m2-m1) / A*um.

[0123] Coating thickness test method: German Mahr C1216 film thickness measuring instrument.

[0124] The porous alumina obtained in the above-mentioned Examples 1 to 8, the comparative samples obtained in Comparative Examples 1 to 6 and the control sample (Comparative Example 1, α-alumina (Suzhou Jinyi New Materials Technology Co., Ltd., 70W04)) were tested for particle size, pore size, specific surface area, surface hydroxyl content, unit thickness coating surface density of the diaphragm coated with the coating, and the charge and discharge rate of the lithium-ion button battery formed by the corresponding diaphragm assembly, and the test results are shown in Table 1.

[0125] The preparation method of the diaphragm is specifically as follows:

[0126] Weigh 100g of alumina powder, 150ml of pure water, 1.74g of dispersant (solid content 46%), add to a high-speed disperser, adjust the speed to 1500rpm, and disperse for 30min. Reduce the speed to 400rpm, add 17.39g of binder (solid content 46%), 30g of thickener (solid content 2%), and 0.8g of wetting agent (solid content 100%) every 15min, and disperse for 30min to obtain the diaphragm slurry. Apply the diaphragm to the required thickness on the coating machine. The base film is selected from PE film. The diaphragm is dried in the shade and cut to the required size. Weigh and measure the thickness of the above diaphragm, and calculate its unit thickness coating surface density.

[0127] Table 1

[0128]

[0129] It can be seen from Table 1 that the porous alumina provided in the present application not only has a lower surface density than conventional alumina under the condition of equivalent coating thickness, but also has a lower surface density per unit thickness than the coating formed by the porous alumina particles obtained in Comparative Examples 1 to 6. It can be seen that the coating provided in the present application has a lower surface density than conventional alumina; in addition, the 5C rate of the button battery based on the coating formed by the porous alumina provided in the present application is significantly optimized.

[0130] The coating thickness, powder proportion and coating volume of the coating on the diaphragm are measured by selecting three points (three points in an equilateral triangle) on each diaphragm sample, calculating the coating surface density based on the detection result of each point, and then calculating the average value to obtain the surface density of the coating. The data acquisition method is shown in Example 1 and Comparative Example 1 in Table 2.

[0131] Table 2

[0132]

[0133] In addition, the inventors also studied the liquid absorption rate, liquid absorption rate and liquid replenishment performance of the diaphragm based on the aluminum oxide provided in the present application, and found that when the D bet When the value is controlled within the range of 0.01~0.02μm, the liquid retention rate, liquid absorption rate and liquid replenishment performance of the resulting diaphragm will be improved to a certain extent.

[0134] The inventors found that when the D of porous alumina bet When the value is controlled within the range of 0.01~0.02μm, after the porous alumina diaphragm absorbs liquid and then is dried in the shade for 12~24h, the electrolyte retention in the diaphragm (the percentage increase in mass compared to the weight of the diaphragm before absorbing liquid) can still reach 85%, or even more than 87%, and its adsorption force on the electrolyte is also strong. The vertical adsorption height of the diaphragm strip with a width of 20mm can reach 12mm. The button battery formed by the diaphragm based on this porous alumina can still maintain a capacity retention rate of more than 85% at a 5C rate. In addition, the inventors tested its 3C rate and 1C rate and found that it can achieve a capacity retention rate of 90% at a 3C rate, and even a capacity retention rate of 95% at a 1C rate, which is beneficial to improving the fast charging performance of the battery. The possible reason may be that when the D of the porous alumina bet When the value is within the specific range of 0.01~0.02μm, the porous alumina can not only store a large amount of electrolyte, but also has good electrolyte replenishment efficiency and replenishment time, which has an effect similar to "slow release" replenishment, and can effectively compensate for the defect of rapid consumption of electrolyte in the battery at high rate, which leads to a significant decrease in capacity retention rate at high rate.

[0135] Among them, the specific test of the liquid retention rate of the diaphragm is as follows:

[0136] The coated diaphragm is cut into several 50 mm × 50 mm squares, which are recorded as AT1, AT2 ... and AL1, AL2 ..., and weighed respectively to obtain the mass of the diaphragm M1; the diaphragm is completely immersed in the electrolyte, and left for a period of time to ensure that the electrolyte is completely absorbed, and then the coated diaphragm is dried in the shade for 12 to 24 hours; the diaphragm after drying in the shade is weighed to obtain the mass of the diaphragm after infiltration M2;

[0137] The liquid absorption rate of multiple coated membranes was calculated according to the following formula, and the average value was taken as the final liquid absorption rate of the coated membrane:

[0138] Diaphragm liquid absorption rate = (M2-M1) / M1×100%

[0139] Among them, the specific test of the liquid absorption rate of the diaphragm is as follows:

[0140] Cut the coated diaphragm into long strips with a width of 20 mm and hang them above the electrolyte with the lower end of the diaphragm in contact with the electrolyte (the height of the diaphragm immersed in the electrolyte is controlled at 3-5 mm). Observe the rising height and rising time of the electrolyte on the diaphragm strip, and calculate the climbing speed of the electrolyte on the diaphragm strip per unit time and the final climbing time.

[0141] The test results are shown in Table 3.

[0142] Table 3

[0143]

[0144] In addition, the applicant further studied the optimization of the porous alumina provided in the present application at different charge and discharge rates, and found that the optimization of the coating formed by the porous alumina provided in the present application is more obvious at high charge and discharge rates, while the optimization at low charge and discharge rates is relatively unobvious. Figure 2 The capacity retention rates of the diaphragms prepared with alumina obtained in Example 1 and Comparative Example 1 at different rates are shown.

[0145] Table 4

[0146]

[0147] It can be seen from Table 4 that the porous alumina provided in the present application improves the capacity retention rate of the battery, especially the capacity retention rate of the battery at high rate is significantly optimized.

[0148] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A porous alumina for battery separator, characterized in that: The porous alumina is an alumina particle with a plurality of mesopores distributed on the surface and inside. The specific surface area of ​​the porous alumina is between 10 and 50 m 2 / g within this range; The ratio D of the specific volume v of the porous alumina to the specific surface area BET of the porous alumina bet Satisfies the following formula: 0.01μm<D bet <0.03μm; The ratio of the short side of the bottom surface of the aluminum oxide particle to the height of the aluminum oxide particle is 1:(0.3-1.5); the pore diameter is 2-50 nm; and the proportion of the pores in the aluminum oxide particle is not less than 60%.

2. The porous alumina for battery separator according to claim 1, characterized in that: The porous alumina includes at least one of α-alumina, θ-alumina, and δ-alumina.

3. The porous alumina for battery separator according to claim 2, characterized in that: The porous alumina does not include γ-alumina.

4. The porous alumina for battery separator according to claim 1, characterized in that: The proportion of the pores in the alumina particles to the alumina particles is determined by the following method: A transmission electron microscope (TEM) image of the aluminum oxide particles is obtained using a transmission electron microscope, the grayscale of the transmission electron microscope image is adjusted so that the grayscale of the pixel with the highest grayscale is adjusted to 255, and the ratio of the total number of pixels with a grayscale not higher than 100 within the range of the aluminum oxide particles in the transmission electron microscope image to the total number of pixels within the range of the aluminum oxide particles in the transmission electron microscope image is counted.

5. The porous alumina for battery separator according to claim 4, characterized in that: The proportion of pores in the alumina particles is not less than 80%.

6. The porous alumina for battery separator according to claim 1, characterized in that: The particle size distribution D50 of the porous alumina is 0.3-20 μm, and the value of D50 / (D90-D10) of the porous alumina is 0.4-1.

7. A battery separator, characterized in that: The battery separator comprises a base film and a coating formed on at least one side of the base film, wherein the porous alumina according to any one of claims 1 to 6 is distributed in the coating.

8. The battery separator according to claim 7, characterized in that: The content of porous alumina in the coating is 75% to 95%, and the surface density of the coating per unit thickness is not higher than 2g / (m 2 ·μm).

9. A battery, characterized in that: The battery separator according to claim 8 is included.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Patent Citations

  • Aluminum oxide for coating ceramic diaphragm of lithium battery and preparation method of aluminum oxide

    CN109336148A

  • Easily dispersed aluminum oxide for ceramic membrane of lithium battery and preparation method thereof

    CN109516782A